Perfil de lípidos y ácidos grasos de Perna viridis, mejillón verde(Mollusca: Bivalvia) en el oriente venezolano y la costa oeste de Trinidad - Koftayan, Tamar (2011)
The species Perna viridis is a highly consumed spe-cies, which fast growth makes it an interesting aquaculture alternative for Venezuelan and Trinidad coasts. With the aim to contribute with its nutritional value information, this study analyzed lipid and fatty acid contents from samples taken in five locations from Eastern Venezuela and three from Trinidad West Coast. Total lipids were extracted and quantified, from a pooled sample of 100 organisms per location, by standard gravimetric methods, and their identification and quantification was done by TLC/FID (Iatroscan system). Furthermore, the esterified fatty acids of total lipid, phospholipids and triacylglycerols were identified and quantified by gas chromatog-raphy. Eastern Venezuela samples from Los Cedros, La Brea and Chaguaramas showed the highest total lipid values of 7.92, 7.74 and 7.53, respectively, and the minimum values were obtained for La Restinga (6.08%). Among lipid composition, Chacopata samples showed the lowest phospholipid concentration (48.86%) and the maximum values for cholesterol (38.87%) and triacylglycerols (12.26%); besides, La Esmeralda and Rio Caribe samples exhibited maximum phospholipids (88.71 and 84.93 respectively) and minimum cholesterol (6.50 and 4.42%) concentrations. Saturated fatty acids represented between 15.04% and 65.55% within total lipid extracts, with maximum and minimum values for La Esmeralda and Chacopata, respectively. Polyunsaturated results resulted between 7.80 and 37.18%, with higher values in La Brea and lower values in La Esmeralda. For phospholipids, saturated fatty acids concentrations varied between 38.81 and 48.68% for Chaguaramas and Chacopata samples, respectively. In the case of polyunsaturated fatty acids, these varied between non detected and 34.51%, with high concentrations in Los Cedros (27.97%) and Chaguaramas (34.51%) samples. For the tria-cylglycerols, the saturated fatty acids composition oscillated between 14.27 and 53.80% with low concentrations for Chacopata and high concentration for La Restinga; the polyunsaturated fatty acids were between 4.66 and 35.55% with lower values for Chacopata and higher values for Chaguaramas samples. P. viridis is recommended for human being consumption, according to the high content of unsaturated fatty acids found for this species.